Mental health problems in unaccompanied young refugees and the impact of post-flight factors on PTSS, depression and anxiety–A secondary analysis of the Better Care study - Hornfeck, Fabienne; Eglinsky, Jenny; Garbade, Maike; Rosner, Rita; Kindler, Heinz; Pfeiffer, Elisa; Sachser, Cedric (Frontiers in Psychology, 2023)
Background: Unaccompanied young refugees (UYRs) show elevated levels of mental distress such as posttraumatic stress symptoms (PTSS), depression, and anxiety. The individual post-arrival situation in the host country plays an important role in increasing or reducing mental health risks for these vulnerable children and youth. The study aims at examining the impact of pre- and post-migration factors on the mental health of UYRs. Methods: A cross-sectional survey of N=131 young refugees (81.7% male, M=16.9 years old) was conducted in 22 children and youth welfare service (CYWS) facilities in Germany. The participants provided information about pre- and post-flight experiences. Standardized measures were used to assess posttraumatic stress symptoms (CATS-2), symptoms of depression (PHQ-9) and anxiety (GAD-7). Daily stressors were assessed with the Daily Stressors Scale for Young Refugees (DSSYR), sociocultural adaptation with the Brief Sociocultural Adaptation Scale (BSAS), satisfaction with social support with the Social Support Questionnaire (SSQ6-G). Results: Our results demonstrated clinical levels of PTSS in 42.0% of the participants, depression in 29.0%, and anxiety in 21.4%. Hierarchical regression analyses revealed that a higher number of traumatic events and social daily stressors predicted higher levels in all three domains of mental health problems. PTSS and anxiety were also predicted by the distress related to the residence status, depressive symptoms were predicted by sociocultural adaptation, less family contact and length of stay. The satisfaction with social support was not a significant predictor in the regression models. Conclusions: UYRs in CYWS facilities are a highly vulnerable population. As traumatic events, daily stressors and level of contact to family directly impacted UYRs mental health, interventions should be trauma-focused, but also contain modules on how to cope with daily stressors. On the policy and practical level, stakeholders in host country are called for establishing measures to reduce post-migration stressors and enhance support for UYRs on all levels.